Pengaruh Model Problem Based Learning terhadap Motivasi Belajar Siswa pada Mata Pelajaran PAI - Azaria Anggun; Fajar Anugrah; Fannisa Aprilia; Tasya Aulia Nazwa; Masyitah Masyitah (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the effect of the Problem Based Learning (PBL) model on students' learning motivation in Islamic Education (PAI) subjects. The background of this research is based on the low motivation of students observed in conventional learning processes. The method used is an experimental design with a pretest-posttest approach, involving 21 students divided into experimental and control groups. The results show that the implementation of the PBL model significantly enhances students' learning motivation, with a higher increase in motivation scores in the experimental group compared to the control group. These findings indicate that the PBL model can create a more engaging and relevant learning environment, leading to increased student motivation. The implications of this research highlight the need for training for teachers in implementing the PBL model to enhance student engagement in PAI learning.